Diagnostic accuracy of post-mortem MRI for thoracic abnormalities in fetuses and children - Arthurs,OJ; Thayyil,S; Olsen,OE; Addison,S; Wade,A; Jones,R; Norman,W; Scott,RJ; Robertson,NJ; Taylor,AM; Chitty,LS; Sebire,NJ; et al. (European Radiology, 2014)
Objectives To compare the diagnostic accuracy of postmortemmagnetic resonance imaging (PMMR) specificallyfor non-cardiac thoracic pathology in fetuses and children,compared with conventional autopsy.Methods Institutional ethics approval and parental consentwas obtained. A total of 400 unselected fetuses and childrenunderwent PMMR before conventional autopsy, reportedblinded to the other dataset.Results Of 400 non-cardiac thoracic abnormalities, 113(28 %) were found at autopsy. Overall sensitivity and specificity(95 % confidence interval) of PMMR for any thoracicpathology was poor at 39.6 % (31.0, 48.9) and 85.5 % (80.7,89.2) respectively, with positive predictive value (PPV)53.7 % (42.9, 64.0) and negative predictive value (NPV)77.0 % (71.8, 81.4). Overall agreement was 71.8 % (67.1,76.2). PMMR was most sensitive at detecting anatomicalabnormalities, including pleural effusions and lung or thoracichypoplasia, but particularly poor at detecting infection.Conclusions PMMR currently has relatively poor diagnosticdetection rates for the commonest intra-thoracic pathologiesidentified at autopsy in fetuses and children, including respiratorytract infection and diffuse alveolar haemorrhage. Thereasonable NPV suggests that normal thoracic appearancesat PMMR exclude the majority of important thoraciclesions at autopsy, and so could be useful in the contextof minimally invasive autopsy for detecting non-cardiacthoracic abnormalities.